Numerical Simulation of Dynamic Damage and Stability of a Bedding Rock Slope under Blasting Load - Yekai Chen; Junhao Xu; Xiaohui Huo; Jinchang Wang (Shock and Vibration)
Blasting excavation of a bedding rock slope is a common problem in highway construction in mountainous areas. Accurate simulation of damage area caused by blasting excavation is of great significance for the subsequent maintenance of slopes. Based on a highway construction project in Guangdong province of China, a tensile and compressive damage model was used to simulate the whole process of blasting excavation of a typical bedding rock slope. The analysis results show that damage first appears just around the blasting hole and then develops to the both sides and the bottom of the blasting hole, and finally a large range of damage appears in the lower part of the blasting hole, and the damage depth on the right-side slope is around 2 m, which is in consistent with the scene. Besides, damage also occurs in the middle of the bedding rock mass of the slope. At the same time, the history analysis of vibration velocity also indicates that tensile failure appears on the right-side slope under the blasting hole. Therefore, the stability of the slope can be assessed by analyzing the distribution of damage factors and the vibration velocity characteristics synthetically. In addition, parameter analysis was also carried out to optimize the blasting design by controlling the blasting load so as to obtain the ideal blasting excavation effect and ensure the stability of the slope under blasting load.